Autores ajuglarados y mester de clerecía - Ramírez Santacruz, Francisco (Verba hispanica, 2013)
While many critics (Ramón Menéndez Pidal, Ian Michael and Colin Smith, among others) have suggested a likely influence of Cantar de mio Cid on the authorof Libro de Alexandre, until now no comprehensive catalogue of concordances has been prepared in order to corroborate this hypothesis. This paper aims to provide the most extensive series of equivalences between these two works. A detailed three stage analysis of the poems reveals strong connections of both a thematic and formal nature. First, the common binomial expressions and similar phraseology in both texts are studied from a rhetorical point of view. Second, the constant dialogue with the listener - which both works share - represents a similarity of technique, that should not be underestimated.Third and finally, the analogous treatment that both poems give to certain themes (the spoils of war, the function of dreams, the relationship between conquerors and conquered, and the heros journey) also reveals an extensive inventory of similarities. This study also confirms that a certain set of poetic habits identified by critics in Libro de Alexandre as a trait common to jongleursis a direct legacy of the Cid, which implies a wide distribution and popularity of the epic poem amongst the clergy. Finally, the results of this comparative analysis show a more intense relationship between the poetics of Spanish epic poetry and mester de clerecía than has been generally acknowledged.
Keywords: Libro de Alexandre; Cantar de mio Cid; Spanish literature; španska književnost; srednji vek; Middle Ages; potujoči pevci; epika